Key Steps to Improve Agribusiness Competitiveness, Part II : Research and Development, Logistics, and Marketing - Walton, Tom (International Finance Corporation, Washington, DC, 2018)
Agriculture is central to emerging market economies. In Africa it accounts for as much as 65 percent of employment and 32 percent of output. Globally, two-thirds of the world’s poor - some 750 million people - work in rural areas. But as economies expand and production shifts to manufacturing and services, agriculture’s share of employment, and gross domestic product (GDP) decreases. At the same time, the broader agribusiness industry - business activities performed from farm to fork - is playing a more important role in growth and development. Improved land rights, better regulation of input and output markets, and better access to seeds and fertilizer are all critical to this transition. In part II, the emphasis is on a shift of research and development (R and D) spending from the public sector to private enterprises in middle-income countries focused on market opportunities related to advanced technologies and knowledge transfers. And a new emphasis on agricultural marketing, logistics, and market data is helping to integrate small farms into agricultural value chains, with higher prices for their products, greater productivity growth, and more sustainable overall development.